Monitoraggio di un gruppo di insetti predatori, i coleotteri carabidi, ai fini della conservazione e dello sviluppo sostenibile dell'agricoltura nel parco nazionale della Sila - Cavaliere, Francesco; Cerra, Maria Carmela; Brandmayr, Pietro; Giglio, Anita (Università della Calabria, 2020)
Agricultural management practices are known to cause lethal and sub-lethal effects on animals inhabiting croplands. The persistence and residual accumulation of pesticides in the soil are detrimental to the environment and pose a risk for human health and for species providing biocontrol ecosystem services. Carabid beetles are useful bioindicators to evaluate the ecological effects of agrochemicals due to their ecological role as predators in farmland. In order to assess the sub-lethal effects at the community, species and organism levels, on non-target species caused by regular pesticide applications, an environmental monitoring was performed over a period of two years, in two sites around the agricultural area to Sila National Park. One site is a conventional farm (39°16'58.05"N, 16°38'43.26"E, 1240 m a.s.l., Torre Garga Farm, Calabria, Italy), it was treated with herbicides, pesticides and fungicides used for pest control. The second site, chosen as control, is an organic farm (39°17'10.28"N, 16°42'28.33"E, 1150 m a.s.l., Macchia di Tuono Farm, Calabria, Italy). To check the direct sublethal effect of field exposure on species abundance and density at the community level, carabid beetles were collected in vivo by pitfall traps and identified using dichotomous keys. To asses the direct sub-lethal effect of field exposure at the organism level, the body size, the constitutive immune responses and genotoxicity we quantified in adults of Harpalus rufipes, a generalist predator taxonomically and ecologically well known, widely distributed and easy to collect in crops. The findings of this study indicated that chemical treatments admitted in the conventionally managed fields have negative effects on the abundance and density of species inhabiting croplands, the low level of PO and lysozyme-like enzyme activities and the DNA damage recorded in haemocytes indicated that field treatments might influence this non-target soil-dwelling species. However, field treatments did not cause morphometric changes in the body size of adults. The reduction of humoral responses and the genotoxic effect recorded on haemocytes may result in an increased susceptibility of this species to pathogens. From an ecoimmunological point of view, a modification of other basic life history traits such as reproduction, dispersal activity and predation may occur with effects on the adult fitness, resulting in changes of the population structure and in a reduction of the biocontrol activity for pest species in agroecosystem.
Università della Calabria. Dipartimento di Biologia, Ecologia e Scienze della Terra Dottorato di Ricerca in Scienze della Vita. Ciclo XXXII
Keywords: Coleotteri carabidi; Pesticidi; Monitoraggio ambientale; Genotossicità